GROWTH RESPONSE AND YIELD OF PURPLE EGGPLANT ON VARIOUS PLANTING MEDIA AND LIQUID ORGANIC FERTILIZER - Maryana, Maryana; S. Padmini, Oktavia; Indri, Nia (Universitas Pembangunan Nasional Veteran Yogayakarta, 2023)
Purple eggplant is a seasonal vegetable that contains a lot of fiber and few calories and is rich in manganese, folate, potassium, vitamins K and C, small amounts of niacin, magnesium and copper. The research aims to determine the composition of various planting media compositions and liquid organic fertilizers that are best for the growth and yield of purple eggplant plants. The research was carried out at the Experimental Garden of the Faculty of Agriculture, National Development University